STRENGTHENING MSMES THROUGH PACKAGING INNOVATION: A COMMUNITY SERVICE PROGRAM IN BAYAN VILLAGE - Delamontano, Eldo; Rahmatuddini, Nurmiza; Suryana, Isabella Muliawati; Naldianti, Dila; Khairunnisa, Khairunnisa; Indah, Minarti; Arfah, Muh (GERVASI: Jurnal Pengabdian kepada Masyarakat, 2026)
MSMEs in Bayan Village, North Lombok, face significant challenges in expanding their market reach due to limited innovation in product packaging, which remains largely traditional and merely functional. This community service program aimed to enhance MSMEs' capacity by introducing packaging innovation as a strategic marketing tool. The primary partners involved 10 local entrepreneurs from the woven fabric, coffee, souvenir, snack, and traditional beverage sectors. The team included academics from UIN Sulthan Thaha Saifuddin Jambi, Barakarsa Foundation and regional volunteers. Employing Participatory Action Research (PAR), activities involved observation, pre-test, an interactive workshop utilizing real product examples, and post-test evaluation. Results demonstrated a 20% increase in participants' knowledge, with average scores rising from 2.00 to 2.40, particularly in branding strength and global market suitability indicators. This program demonstrates that participatory and example-based training can effectively shift the mindset of MSME actors toward a more strategic approach in managing their products' visual identity.